The Impact of Parent–Child Attachment on Self-Injury Behavior: Negative Emotion and Emotional Coping Style as Serial Mediators - Tao, Yun; Bi, Xiao-Yan; Deng, Min (Frontiers in Psychology, 2020)
In order to explore the relationship between parent-child attachment, negative emotion, emotional coping style and self-injury behavior, 662 junior high school students in four junior middle schools in China’s Yunnan Province were investigated with parent-child attachment questionnaire, adolescent negative emotion questionnaire, emotional coping style scale and adolescent self-injury behavior scale. As a result, two mediate models were founded to explain how parent-child attachment affects self-injury behavior. Negative emotion and emotional coping style play serial mediates roles respectively in mother-child and father-child attachment models. The results show that negative emotion mediates between self-injury behavior and both father-child and mother-child attachment, while emotional coping style only functions between father-child attachment and self-injury behavior. By means of bootstrap analysis, negative emotion and emotional coping style represent serial mediates role concerning the impact of parent-child attachment on self-injury behavior. By comparison, the father-child and mother-child attachment have different mediate models: the former relies on emotional coping style, while the latter is associated with emotional experiences. This implies that parent-child attachment has different mechanisms in triggering self-injury behavior, which is in line with the hypothesis of attachment specificity.